Analogies of the Qi formula for some Dowling type numbers - Corcino, Roberto B.; Malusay, Jeneveb T.; Cillar, Joy Antonette; Rama, Gladys Jane; Silang, Oscar Vincent; Tacoloy, Ianna Marie (Utilitas Mathematica, 2019)
In the paper, the authors establish explicit formulas for the Dowling numbers and their generalizations in terms of generalizations of the Lah numbers and the Stirling numbers of the second kind. These results generalize the Qi formula for the Bell numbers in terms of the Lah numbers and the Stirling numbers of the second kind. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.